Best Answer

It is x+9, provided that x is not -8.

Q: What is the answer to x2 plus 17x plus 72 divided by x plus 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x + 4)(x + 13)

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

x3-x2+5x-1 with remainder 7, which the final answer would be written as:x3-x2+5x-1+[7/(4x+3)]

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

(x+13)(x+4)

Related questions

(x + 4)(x + 13)

(x + 1)(x + 3)(x - 5)

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

x3-x2+5x-1 with remainder 7, which the final answer would be written as:x3-x2+5x-1+[7/(4x+3)]

x2-17x-18 divided by x+1Factorising the quadratic expression gives you:(x-18)(x+1) which when divided by x+1 leaves you with: x-18

(x + 3)(4x + 5)

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

(x + 8)(x + 9)

(x+13)(x+4)

i got 42 divided 7x

Assuming this expression equals zero, it factorises as (x + 4)(x + 13) making x either -4 or -13.

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)